Analisis Yuridis Pelanggaran Etik pada Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 - Yunita Octa Wulandari, Anugrah (Proceedings Series on Social Sciences & Humanities, 2024)
Judges who function as executors and spearheads the justice system and liaise with the community, are expected to have high expertise in considering and making legal decisions about cases. A judge must abide by the applicable code of ethics while performing his duties. A judge will be punished based on a violation of his professional code of ethics. The latest case regarding violations of the code of ethics is the case of Chief Justice of the Constitutional Court Anwar Usman, who has been proven to have violated the judge's professional code of ethics related to Decision Number 90/PUU-XXI/2023. This study aims to determine how accountable a judge who violates the code of professional ethics and how the Honorary Panel of the Constitutional Court (MKMK) acts in handling cases where constitutional judges violate the code of ethics. Normative juridical methods were used in the study. This method refers to applicable laws and regulations, as well as community standards. This approach refers to applicable laws and regulations, which include principles, principles, and doctrines.